Influência de recursos musculoesqueléticos do indivíduo no desempenho em uma tarefa de agachamento unipodal com demanda de velocidade e precisão - Vanessa Aparecida Cardoso (2017)
Tasks involving squatting have been widely used for assessing functional performance and ability of individuals to stabilize the lower limbs. Traditionally, these tasks have been performed without constrain the pattern of movement adopted by the individual. A squatting task that imposes a demand of precision and velocity to be accomplished may require a better dynamic alignment (movement control in different motion planes) of the lower limb to fulfill the task requirements. The capability of movement control in the different motion planes during squatting seems to be related to the musculoskeletal resources of the individual. The objective of the present study was to evaluate the influence of stiffness, mobility, alignment and muscle strength, related to the hip, knee and ankle-foot joints, upon the performance in a single leg squat task with simultaneous demand of velocity and precision. Clinical measurements were used to quantify the hip passive stiffness, the dorsiflexion range of motion, the forefoot alignment and the muscle torque of the knee extensors (EXT) and flexors (FLEX) and the hip abductors (ABD) and lateral rotators (LR). The task involved squatting with the aim of directing a laser towards two targets with diameters of 10 and 3 cm and distances between the targets of 20 and 27 cm, resulting in three conditions: 10/20, 10/27 e 3/27. The movement time to accomplish each of the three conditions was measured with a digital chronometer. Only the muscle torques of the hip and knee joints showed bivariate association to the duration of the movement in all task conditions (r -0.38; p 0.020). Hierarchical regression models identified that higher torque values of the EXT (R2 0.20), FLEX (R2 0.21) and LR (R2 0.14) were significant predictors of a lower movement time. However, these torque contributions were different for each task condition. The results showed that the capacity of the knee and hip muscles to generate force seems to be a resource that influences healthy subjects' performance in a single leg squat task that involves the simultaneous demand of velocity and precision.